Stress and strain distribution in three different mini dental implant designs using in implant retained overdenture: A finite element analysis study - Aunmeungtong W. (2017)
© 2016 CIC Edizioni Internazionali Unauthorized reproduction of this article is prohibited. Finite Element Analysis (FEA) has been used for prediction of stress and strain between dental implant components and bone in the implant design process. Purpose. Purpose of this study was to characterize and analyze stress and strain distribution occurring in bone and implants and to compare stress and strain of three different implant designs. Materials and methods. Three different mini dental implant designs were included in this study: 1. a mini dental implant with an internal implant-abutment connection (MDIi); 2. a mini dental implant with an external implant-abutment connection (MDIe); 3. a single piece mini dental implant (MDIs). All implant designs were scanned using micro-CT scans. The imaging details of the implants were used to simulate models for FEA. An artificial bone volume of 9x9 mm in size was constructed and each implant was placed separately at the center of each bone model. All bone-implant models were simulatively loaded under an axial compressive force of 100 N and a 45-degree force of 100 N loading at the top of the implants using computer software to evaluate stress and strain distribution. Results. There was no difference in stress or strain between the three implant designs. The stress and strain occurring in all three mini dental implant designs were mainly localized at the cortical bone around the bone-implant interface. Oblique 45° loading caused increased deformation, magnitude and distribution of stress and strain in all implant models. Conclusions. Within the limits of this study, the average stress and strain in bone and implant models with MDIi were similar to those with MDIe and MDIs. The oblique 45° load played an important role in dramatically increased average stress and strain in all bone-implant models. Clinical implications. Mini dental implants with external or internal connections have similar stress distribution to single piece mini dental implants. In clinical situations, the three types of mini dental implant should exhibit the same behavior to chewing force.